Closed loop small bowel obstruction due to mid urethral sling mesh - Alaoudi, Marwan; Devanabanda, Bhavana; Haj, Roland; Louis, Martine; Shah, Darshak (International Surgery Journal, 2020)
Closed loop small bowel obstruction is a surgical emergency, which when left untreated leads to vascular compromise resulting in intestinal ischemia, necrosis and perforation. We report the case of a 61 years old female with past surgical history of hysterectomy and a mid-urethral sling, who presented to the emergency department for abdominal pain and obstipation. She was found on imaging to have a closed loop small bowel obstruction. An exploratory laparotomy revealed an adhesive band encompassing the distal terminal ileum, visceral peritoneum and the Mid‐urethral slings mesh. This is a rare complication that, to our knowledge, has not been reported in the surgical literature. This paper will discuss the clinical presentation, diagnostic studies, therapeutic intervention and outcome of this unique case.